Pelatihan Aplikasi ANSIS (Analisa System) bagi Karyawan Credit Analis Mandala Dalam Pemberian Kredit Motor - Sarwindah, Sarwindah; Marini, Marini; Sugihartono, Tri; Yurindra, Yurindra; Safitri, Jesi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
The development of information technology is very influential for the progress of a business, one of which is in organizations or companies such as finance. Where Mandala is a leasing company engaged in motorcycle credit services for credit applicants and taking advantage of credit interest payments. Mandala is a company that upholds its commitment to provide the best service to consumers and business partners, through optimal services supported by directed, integrated and sustainable human resource management, one of the most important. With the help of computers can make it easier for anyone to carry out various activities effectively and efficiently. Here the team conducts training for credit analysts in Mandala by making applications with the aim of being an alternative for credit analysts to help make decisions faster with the ANSIS application. In other words, knowledge of computers is one of the most important needs in today's era. One of them is in an effort to assist Credit Analysts in consumer decision-making activities in terms of creditworthiness, a computer-based decision support system model is needed that can provide convenience in conducting analysis